Correction: The origin of room temperature ferromagnetism mediated by Co–VZn complexes in the ZnO grain boundary. Issue 102 (19th October 2016) - Sasikala Devi, Assa Aravindh; Roqan, Iman S.
Abstract : Correction for 'The origin of room temperature ferromagnetism mediated by Co–VZn complexes in the ZnO grain boundary' by Assa Aravindh Sasikala Devi and Iman S. Roqan, RSC Adv., 2016, 6, 50818–50824.